Synovial Fluid Biomarker Concentrations in Knees with Symptomatic Meniscus Injury Compared to Asymptomatic Contralateral Knees. Issue 7 (29th July 2019) - Clair, Andrew; Kingery, Matthew T.; Anil, Utkarsh; Kenny, Lena; Strauss, Eric Jason
Objectives: Changes in the joint microenvironment following an intra-articular injury have been implicated in the pathogenesis of knee osteoarthritis. Few studies have evaluated alterations in the joint microenvironment in the setting of meniscus injury. The purpose of the current study was to determine the changes in synovial fluid biomarker concentrations caused by meniscus pathology by comparing samples from injured, symptomatic knees to samples from asymptomatic contralateral knees. Methods: Patients undergoing surgery for unilateral meniscus injury were prospectively enrolled in this institutional review board approved study from October 2011 to December 2016. A cohort was formed consisting of patients that had synovial fluid samples collected from both the injured and contralateral uninjured knee at the time of arthroscopic surgery. Patients with ligamentous injury of the knee were excluded from the current analysis. Synovial fluid samples were collected just prior to incision and the concentrations of 10 biomarkers of interest were determined using a multiplex magnetic bread immunoassay. Results: The current analysis included synovial fluid samples from 82 knees (41 operative and 41 contralateral knees) from 41 patients undergoing arthroscopic surgery to treat a symptomatic meniscus injury. The mean age of patients was 49.86 +/- 11.75 years. Based on linear mixed effects models, there were significantly greater concentrations of 4 of the 5 pro-inflammatory biomarkers in symptomatic knees compared to asymptomatic knees when controlling for the duration of symptoms, BMI, age, and the random effects of by-patient variability. Knees with symptomatic meniscus injuries had 126.8 times greater concentration of IL-6, 2.7 times greater concentration of MCP-1, 2.0 times greater concentration of MIP-1beta, and 5.4 times greater concentration of MMP-3 compared to the contralateral, asymptomatic knee (Table 1). When controlling for the chronicity of the injury, presence of synovitis, and age of the patient, knees with concomitant high-grade cartilage lesions (ICRS 3 or 4) were associated with 2.1 times greater concentration of MCP-1, 1.9 times greater concentration of MIP-1beta, and 3.4 times greater concentration of VEGF compared to knees with concomitant low-grade cartilage lesions (ICRS 1 or 2). When controlling for the other variables, the presence of synovitis was associated with an 89.5% lower concentration of TIMP-1 compared to operative knees without synovitis. The age of the patient was found to affect the concentrations of IL-6, MCP-1, and VEGF. For all knees included in the study, each 1 year increase in age was associated with a 6% increase in IL-6, 3% increase in MCP-1, and 4% increase in VEGF (Figure 1). Conclusion: This study is the first that examines the synovial fluid biomarker concentrations in the setting of a symptomatic isolated meniscus injury. We demonstrated that 4 of the 5 proinflammatory biomarkers that were tested are found in greater concentration in the symptomatic knee. Furthermore, we described the effects of associated cartilage damage, synovitis, and patient age on biomarker concentrations. Understanding the implication of these alterations in the intra-articular microenvironment in the setting of meniscal pathology may hold the key to identifying treatment targets in an effort to prevent the onset of post-meniscectomy osteoarthritis. Variable RANTES IL-6 MCP-1 MIP-1β MMP-3 TIMP-1 TIMP-2 IL-1Ra VEGF bFGF Operative Knee 1.56 126.76*** 2.72* 2.00* 5.35* 2.00 0.86 1.26 2.84 0.63 log Duration 1.07 2.12* 1.01 0.99 1.04 1.20 1.00 0.82 0.95 1.03 BMI 1.01 0.93 1.03 1.01 1.03 1.02 1.00 1.00 1.01 1 Age 1.01 1.06** 1.03** 1.01 1.02 1.03 1.03 1.01 1.04* 0.98 Knee*log Duration 0.93 0.28** 0.75 0.93 0.81 0.93 1.29 1.05 0.76 0.94